2017
DOI: 10.1189/jlb.3ab0417-159rr
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid synthase regulates the pathogenicity of Th17 cells

Abstract: T cell activation and effector function is characterized by changes in metabolism. Altered metabolism is common to almost all types of activated T cells, but fatty acid synthesis seems to especially drive the formation of Th17 cells. Indeed, research has demonstrated that inhibition of early fatty acid synthesis through targeting of acetyl-CoA carboxylase (ACC1) can inhibit Th17 cell formation and instead promote the generation of regulatory T cells. Fatty acid synthase (FASN) is downstream of ACC, and previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 32 publications
2
52
0
Order By: Relevance
“…FA, in the form of triglycerides, phosphoglycerides or sphingolipids, are directly involved in T cell activation and proliferation as key components of cell membranes, signaling molecules and energy-yielding substrates. However, FASN inhibition also promoted IFN-γ production by Th1 and Th1-like Th17 cells, which is different from the effect of ACC inhibition [103]. Furthermore, exogenous FA rescued defective blasting and survival of ACC1-deficient CD8 + T cells in vitro [101].…”
Section: Lipid Synthesismentioning
confidence: 76%
See 1 more Smart Citation
“…FA, in the form of triglycerides, phosphoglycerides or sphingolipids, are directly involved in T cell activation and proliferation as key components of cell membranes, signaling molecules and energy-yielding substrates. However, FASN inhibition also promoted IFN-γ production by Th1 and Th1-like Th17 cells, which is different from the effect of ACC inhibition [103]. Furthermore, exogenous FA rescued defective blasting and survival of ACC1-deficient CD8 + T cells in vitro [101].…”
Section: Lipid Synthesismentioning
confidence: 76%
“…Inhibition of fatty acid synthase (FASN) also reduced EAE severity, with direct evidence from adaptive transfer that this effect is Th17-dependent. However, FASN inhibition also promoted IFN-γ production by Th1 and Th1-like Th17 cells, which is different from the effect of ACC inhibition [103]. The specific mechanisms by which FA synthesis regulates CD8 + T cell survival or inflammatory CD4 + T cell polarization have not yet been elucidated.…”
Section: Lipid Synthesismentioning
confidence: 81%
“…257 Similar to ACC1, FASN inhibition also reduced Th17 cell polarization, but it also uniquely boosted IFN-γ production by Th1 and Th1-like Th17 cells. 258 Again, it is not clear whether these differences are due to experimental differences or if they reflect the different roles of the metabolites produced by the two enzymatic reactions. Furthermore, it is still unknown how FA synthesis regulates CD8 + T cell survival or inflammatory CD4 + T cell polarization.…”
Section: Lipid Synthe S Ismentioning
confidence: 99%
“…FAS also plays an extended role in affecting the immune response of Th17 cells, which commonly play dual roles in the physiological immune response and autoimmunity . Subsequent studies have demonstrated that both ACC1 and FASN participate in the regulation of pathogenicity in Th17 cells . Recently, Wang et al proposed an FAS‐related mechanism for regulating this balance.…”
Section: Regulation Of Fas In Different Immune Cell Subsetsmentioning
confidence: 99%
“…61,62 Subsequent studies have demonstrated that both ACC1 and FASN participate in the regulation of pathogenicity in Th17 cells. 60,63 Recently, Wang et al proposed an FAS-related mechanism for regulating this balance. These researchers discovered that CD5 molecule like/Apoptosis inhibitor of macrophage (CD5L/AIM) signalling not only regulates both the ratio of polyunsaturated fatty acids (PUFAs) to saturated fatty acids (SFAs) and FAS-based cholesterol synthesis but also affects retinoid-related orphan nuclear receptor γt (RORγt), a member of the nuclear receptor family of transcription factors, in a ligand-dependent manner.…”
Section: Fas Regulation In T Cellsmentioning
confidence: 99%